Antioxidant activities and emulsifying properties of porcine plasma protein hydrolysates modified by oxidized tannic acid and oxidized chlorogenic acid. (April 2019) - Chen, Yichun; Jiang, Shuai; Chen, Qian; Liu, Qian; Kong, Baohua
Graphical abstract: Highlights: Porcine plasma protein hydrolysates interacted with oxidized phenolic compounds. The interaction occurred via covalent, disulphide, and hydrogen bonds. Modified porcine plasma protein hydrolysates had higher antioxidant activities. Modified porcine plasma protein hydrolysates had higher emulsifying stability. It also had decreased emulsifying activity due to lower surface hydrophobicity. Abstract: Physicochemical characteristics, antioxidant activities and emulsifying properties of porcine plasma protein hydrolysates (PPPH) modified with oxidized tannic acid (OTA) or oxidized chlorogenic acid (OCA) were investigated. The formation of complexes was showed by increased turbidity, and both OTA and OCA were covalently attached to PPPH as shown by the significantly decrease in free amino group contents ( P < 0.05). Fourier transform infrared spectroscopy also indicated cross-linking between PPPH and OTA or OCA through hydrogen bonds. More importantly, compared with PPPH alone, modification of OTA or OCA endowed PPPH with a higher emulsifying stability index and greater antioxidant activities. However, the emulsifying activity index of PPPH significantly decreased after modification ( P < 0.05), which is associated with lower surface hydrophobicity. These results suggest that PPPH-OTA and PPPH-OCA complexes could be used as efficient antioxidants and potential emulsifiers in emulsion-food systems.